ANALISIS KESALAHAN PENGGUNAAN KATA KERJA TRANSITIF DAN INTRANSITIF BAHASA JEPANG PADA MAHASISWA TINGKAT II PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Fitria Sanimah Rahmawati; Sri Wahyu Widiati; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research describes about using an error of transitive and intransitive verbs are done by students in second grade of Japanese Program in Riau University. This research uses a descriptive method. This theory which is used for error analysis and linguistic theory of jidoushi tadoushi . The data is an error gets from written questionnaire test form on bunpou subject. While the factor of an error data gets from interview. Based on the data analysis can be concluded that the form of the most common error is when selecting verb in the sentence of tadoushi or jidoushi . This caused of students still difficult for which different between jidoushi and tadoushi.Keyword : error analysis, jidoushi, tadoushi